Electrochemical Determination of Dopamine by a Reduced Graphene Oxide–Gold Nanoparticle-Modified Glassy Carbon Electrode. (21st September 2016) - Chen, Ting; Tang, Lina; Yang, Fan; Zhao, Qiang; Jin, Xin; Ning, Yong; Zhang, Guo-Jun
ABSTRACT: A novel electrochemical aptasensor is reported for the label-free determination of dopamine by electrochemically reduced graphene oxide and a gold nanocomposite with a ribonucleic acid (RNA) aptamer. The nanocomposite was fabricated by layer-to-layer electrochemical deposition. The aptamer was immobilized on the surface of the gold nanoparticles through the formation of thiol–gold bonds. Dopamine was determined through specific interaction with the immobilized aptamer. The redox activity of the analyte enabled direct electrochemical analysis. The conductivity and structure of the nanocomposite were characterized by cyclic voltammetry and scanning electron microscopy. In contrast to bare or reduced graphene oxide-modified electrodes, the nanocomposite-modified electrode significantly enhanced the current response. The electrochemical aptasensor provided a detection limit of 0.13 µM with a linear dynamic range from 0.5 to 20 µM. In addition, the sensor was shown to provide high selectivity and satisfactory stability for the determination of dopamine in the presence of analogs and in human serum.